Alginate-modified mesoporous bioactive glass and its drug delivery, bioactivity, and osteogenic properties - Yao, Haiyan; Luo, Jun; Deng, Yunyun; Li, Zhihua; Wei, Junchao (Frontiers in Bioengineering and Biotechnology, 2022)
Mesoporous bioactive glass (MBG) is widely used in bone tissue repair and drug loading. However, burst release of drug and poor compatibility with other materials limited its application. It is an effective way to modify MBG with polymer brush to improve the properties. Herein, alginate-modified MBG was prepared, then the effects of ALG on the properties of MBG were investigated. The results demonstrate that ALG could improve the drug loading efficiency, prolong drug release times, and make the orderly deposition of apatite on the surface of MBG. Furthermore, MBG@ALG significantly promoted the osteogenic differentiation of MC3T3-E1 cells, demonstrating that surface modification of MBG by ALG can improve its properties, which will further broad the application of MBG in tissue engineering.